An unusual cardiac mass: Echocardiography, computed tomography, and magnetic resonance imaging. Issue 5 (May 2016) - Pergola, Valeria; Al-Admawi, Mohammed; Fadel, Bahaa; Di Salvo, Giovanni
Abstract: Cardiac tuberculosis is rare. We report an unusual case of cardiac tuberculoma diagnosed in vitam in a 38-year-old woman, with end-stage renal disease and discovered to have mediastinal tuberculosis in 2013. She presented to the emergency department complaining of fever and chills during hemodialysis. A cardiac mass suggestive of tuberculoma was found in the right atrium using echocardiography, computed tomography scan, and cardiac magnetic resonance. Sputum culture was positive for acid fast bacilli. The patient received anti-tuberculosis therapy with improvement of symptoms and reduction of the mass. <Learning objective: Cardiac masses are not infrequently found in right atrium, especially in patients under hemodialysis. In patients known to have tuberculosis the differential diagnosis should include cardiac tuberculoma.>